Kombinasi Metode Certainty Factor dan Forward Chaining untuk Identifikasi Jenis Kulit Wajah Berbasis Android - Syavira Cahyaningsih; Agung Triayudi; Ira Diana Sholihati (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Using skincare and facial skin care must be in accordance with the type of facial skin, because if it is not suitable, it can cause problems such as facial skin breakouts, dry skin, irritated skin, and acne prone skin. To find out the type of facial skin, you have to do an examination with a skin and genital specialist, but the high cost of consultation and the long queue process is an obstacle for everyone. Therefore, the authors created an expert system to identify facial skin types using a combination of certainty factor methods with forward chaining techniques. The diagnostic results from calculations using an expert system application and the results of manual calculations from one of the respondent data from 100 respondent data, namely producing the same level of confidence, each of which produces a percentage of 99.45% and the diagnostic results state that the user has a normal skin type.